Mechanisms of Antibiotic Failure During Staphylococcus aureus Osteomyelitis - Gimza, Brittney D.; Cassat, James E. (Frontiers in Immunology, 2021)
Staphylococcus aureus is a highly successful Gram-positive pathogen capable of causing both superficial and invasive, life-threatening diseases. Of the invasive disease manifestations, osteomyelitis or infection of bone, is one of the most prevalent, with S. aureus serving as the most common etiologic agent. Treatment of osteomyelitis is arduous, and is made more difficult by the widespread emergence of antimicrobial resistant strains, the capacity of staphylococci to exhibit tolerance to antibiotics despite originating from a genetically susceptible background, and the significant bone remodeling and destruction that accompanies infection. As a result, there is a need for a better understanding of the factors that lead to antibiotic failure in invasive staphylococcal infections such as osteomyelitis. In this review article, we discuss the different non-resistance mechanisms of antibiotic failure in S. aureus. We focus on how bacterial niche and destructive tissue remodeling impact antibiotic efficacy, the significance of biofilm formation in promoting antibiotic tolerance and persister cell formation, metabolically quiescent small colony variants (SCVs), and potential antibiotic-protected reservoirs within the substructure of bone.